Multilingual Ontology Learning Algorithm for Emails - Beseiso M.; Ahmad A.R.; Ismail R.; Taher M. (Springer Verlag, 2023)
The e-mails used for personal or business proposals are becoming more and more difficult to manage. The abundant/overhead of e-mails and the lack of assistance from e-mail clients will certainly lead to losing tracks of information contained in e-mails. The multilingual nature of e-mails makes this situation even worse. In this research, we have explained the necessity for utilizing multilingual ontology learning processes to solve this problem. We have proposed the multilingual ontology learning algorithm for semantic email. The proposed algorithm is designed to handle the unstructured emails. This will lead to intelligent applications and information extraction for email users while keeping the semantic layer opaque to the end user. Springer-Verlag Berlin Heidelberg 2013.